Uganda Oil Revenue Management : Closing Gaps in the Fiscal and Savings Frameworks to Maximize Benefits - World Bank (World Bank, Washington, DC, 2020)
After Uganda enjoyed two decades of strong growth and poverty reduction in the 1990s and early 2000s, its economy slowed down, and social progress decelerated amid a steady increase of the population. Several constraints continue to undermine progress and social and economic transformation in Uganda. The start-up of oil production and revenues has the potential to accelerate growth by addressing some of the constraints to economic transformation, but it has to be managed well. Actual revenues from oil will depend on levels of production and international oil, with significant impact on government revenue, exports, and investmentsMaximizing the benefits from oil revenues requires maximizing efficiency across the entire revenue chain. Several analytical and technical assistance programs have recommended specific reforms to help Uganda maximize the dividends from its oil. This paper reassesses the adequacy of Uganda’s public finance systems in providing an appropriate fiscal framework for determining spending as well as setting aside and managing savings for future generations. The rest of the paper is organized in three sections. Section 2 provides an update on the state of development of Uganda’s oil sector. Section 3 discusses the current fiscal framework and what would need to be adjusted before the oil revenue starts flowing. Section 4 delves into the institutional design and operational management of the petroleum revenue investment reserve, and how it could be turned into a genuine SWF for Uganda.